In-depth Training in Calculus Material for MA/Equivalent Teachers in the Madrasah Aliyah VI Garut Working Group - Nuraeni, Reni; Afriansyah, Ekasatya Aldila; Puspitasari, Nitta; Sofyan, Deddy; Hasanudin, Hasanudin; Fikri, Fikri; Lestari, Liya (Fakultas Kewirausahaan Universitas Garut, 2023)
This training was conducted to improve teacher competence, especially in the aspect of deepening the Calculus material. This training provides ways to solve mathematical problems related to Calculus which are not usually given at the secondary school level. The training materials cover Inequality, Drawing Functions Graphs, and Sure Integrals. Based on the results of filling out the training evaluation questionnaire, the teachers gave a positive response and were satisfied because they got more knowledge and insight about the concept of solving Calculus problems that are not usually given at the high school level. It is expected that the teachers can apply the knowledge that has been obtained for the development of learning in the classroom and be able to facilitate students to gain knowledge and have comprehensive mathematical abilities.